Islamic Family Law Reform: Iddah for Husbands as an Effort for Gender Equality - Ruby Isla; Asep Kurniawan; Lita Amelia (Indonesian Journal of Islamic Law, 2023)
This research explores the implementation of iddah for husbands as part of Islamic family law reform to achieve gender equality in Indonesia. Qualitative research methods with a descriptive-analytical approach were used to examine this concept through literature studies and in-depth interviews with legal and psychology experts. The research results show that although the traditional concept of iddah does not regulate a waiting period for husbands, implementing iddah for husbands can provide emotional and psychological benefits, as well as help achieve equality of rights and obligations between husband and wife. Implementation of iddah for husbands also requires support through awareness campaigns, counseling services and a clear legal framework. Therefore, legal reform that includes iddah for husbands is proposed as an important step in creating justice and prosperity in Muslim families in Indonesia.